Shadow economy, energy consumption, and ecological footprint in Indonesia - Irsan Hardi; Mohd Afjal; Muhlis Can; Ghalieb Mutig Idroes; Teuku Rizky Noviandy; Rinaldi Idroes (Sustainable Futures)
The shadow economy consists of economic activities that take place without government oversight, often bypassing energy efficiency standards, leading to higher energy consumption and greater ecological footprints. This study examines the impact of the shadow economy and energy consumption on Indonesia's ecological footprint using the ARDL model and various robustness check methods. Results indicate that both factors positively contribute to increasing the ecological footprint. Economic growth and population density, included in the model, also positively impact the ecological footprint, exacerbating strain on natural resources and ecosystems through unsupervised human activities. Policy recommendations are provided to address these findings.